Efektivitas konseling kelompok dengan teknik modeling simbolik berbasis TPACK dalam meningkan kecerdasan emosi anak usia dini - Swasti Indrayani; Ni Ketut Suarni; Nyoman Dantes (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2023)
This study was conducted with the aim to examianting the effectiveness of group counselling of TPACK-based symbolic modelling techniques to improve children's emotional intelligence. The research was conducted at Tunas Bangsa Kindergarten A. The research sample used random sampling technique. Determination of the experimental class as a sample of this study using lottery technique, the number of samples taken as many as two classes with 8 students from Kindergarten A2 and 11 people from Kindergarten A1. The experiment was carried out with experimental preparation stages by compiling research instruments, trials, observations, preparing RPLBK counselling guidance services and giving Pre-Test, then implementing experiments and finally the experiment ended. The independent variables in this study are group counselling (A) modelling techniques (A1) and TPACK (A2). The dependent variable (Y) in this study is social and emotional intelligence. Data collection methods were conducted through questionnaires. The data analysis technique used t-test. The results showed that the TPACK-based modelling technique group counselling model is effective for stabilising students' emotional intelligence and there is a significant difference in effectiveness between the TPACK-based modelling technique counselling model and the modelling technique without TPACK-based to stabilise kindergarten children’s emotional intelligence.